BAND A LETTER FROM LOVE BROKEN HEARTED ALLIZE WEBSITE DESIGN USING MACROMEDIA DREAMWEAVER 8 - Ryan Ashari Arham; Irfan Irfan, Skom, MM (Jurnal Sistem Informasi, 2007)
This explains the scientific writing about the band Website design A Broken HeartedLove Letter from Allize using Macromedia Dreamweaver 8. The design of this websiteby using the MySQL database is integrated with Macromedia Dreamweaver and PHPprogram, which consists of a table in which table guest_book fruit.By designing and creating a website and placing it into a server, which can be accessedby the public with easy and quick to obtain information about the Broken Hearted BandA Love Letter from Allize.Therefore, using Macromedia Dreamweaver 8, PHP, and MySQL in designing andcreating websites A band Broken Hearted Love Letter from a dynamic web-based Allizato facilitate the public in obtaining information about the band A broken Hearted LoveLetter from Allize quickly and easily.